Use of Urine Antigen Testing for Blastomyces in an Integrated Health System - Baumgardner, Dennis J. (J Patient Cent Res Rev, 2018)
PURPOSE: Blastomycosis, an endemic fungal infection, mimics many other diseases. We explored the use of Blastomyces urine antigen (BuAg), reportedly the most sensitive noninvasive test, in clinical practice and compared it to other noninvasive tests. METHODS: A total of 836 BuAg tests performed on unique patients (first test only) at one large integrated health system from June 2013 to May 2016 were retrospectively reviewed to examine test characteristics and demographic features. Of these, 100 cases from 2015, a year containing a large local blastomycosis outbreak, were randomly selected for detailed analysis. RESULTS: Demographics for the BuAg-tested population: mean age 54.9 years, 55.0% male, 78.9% white, 213 zip codes represented. Test results were positive in 49 of 836 (5.9%, across 43 zip codes); 16 of the 49 (32.7%) stemmed from the 2015 outbreak. BuAg-positive patients were younger than those who tested negative, even with outbreak subjects removed (48.1 vs 56.7 years, P=0.008); and Asians and males were overrepresented. Sensitivity/specificity/positive predictive value of BuAg test was 87.9%/97.9%/76.3%, respectively, based on 33 culture-positive cases. Only 2 of 20 culture-positive cases were found positive by Blastomyces antibody (Ab) immunodiffusion (ID) test and 0 of the other 18 by Ab complement fixation (CF). Of those with positive BuAg who were co-tested, 16.1% were positive by Ab ID and 3.9% by Ab CF. Histoplasma urine antigen was co-performed with BuAg in 578 patients (69.1%) and positive in 25 (4.3%); 16 of these 25 (64.0%) also were BuAg-positive (ie, known cross-reactivity). Of the 100 patients examined for index illness details, 7 (6 BuAg-positive) were ultimately diagnosed with blastomycosis, 7 other fungal disease, 26 noninfectious lung disease, 22 pneumonia, 5 skin lesions, 6 malignancies, 3 mycobacteria, 11 other, and 1 unknown. Of 100, 12 were tested by BuAg based on symptoms. CONCLUSIONS: Blastomyces urine antigen is commonly used for work-up of broad differential diagnoses or known exposures. Not adding Ab ID/CF diagnostic tests ($80 each) to the BuAg test saves money without losing sensitivity.